Sustainable supply chain practices: an empirical investigation on Indian automobile industry. Issue 1 (2nd January 2016) - Gopal, P.R.C.; Thakkar, Jitesh
Abstract : The purpose of this research study is to analyze sustainable supply chain (SSC) management practices for Indian automobile industry and to identify the critical factors for its successful implementation. Despite the fact that SSC has been frequently promoted as a means of improving business competitiveness, little empirical evidence exists in the literature validating its positive link with organizational performance. Sustainable supply chain practices (SSCP) not only help in reducing environmental degradation but it also has social and economic implications (as per tipple bottom line approach). For this purpose, empirical data is collected to measure the SSCP prevailing in Indian automobile industry. A structural equation modeling technique is used to build the measurement and structural models. Later, statistical estimates are used to validate the model that has been built. The data analysis helps to determine whether to accept or reject the hypothesis that has been stated based on the structural model. The result shows how SSCP are correlated and help in improving the supply chain performance among the industries being surveyed. It is also observed that environmental and social performance have a positive relationship with economic performance.